Parmenides. życie jest snem bytu (Parmenides: Life Is a Dream of Being) - Adam Drozdek (Analiza i Egzystencja, 2011)
Death is not a departure of the soul from the body – in can be so only in the road ofopinion – but a departure of the body from the soul, as it were, that is, the rectificationof cognition, having the mind to rely completely on the road of truth, wherebythe opinions fall off and all the illusions they bring into the soul disappear as well.However, to retain the true monistic character of the system, the immortality ofthe soul has to be denied. Humans are temporarily brought into being as thoughtsof Being or as its dream, and eventually disappear since what is important, is theunity of Being.